The framing of power in climate change adaptation research. (1st September 2019) - Woroniecki, Stephen; Krüger, Ruth; Rau, Anna‐Lena; Preuss, Maren Stefanie; Baumgartner, Nora; Raggers, Sanne; Niessen, Laura; Holländer, Lars; Beyers, Felix; Rathgens, Julius; Wagner, Kai Christian; Habigt, Lisa; et al.
Abstract: Power mechanisms and structures shape climate change adaptation outcomes, the measures adopted, and who is identified as requiring adaptation support. But to what extent does research recognize such power‐adaptation linkages? Based on a systematic literature review, we enquire if and how the framing of power matters for adaptation research and what the implications may be for practice. Our enquiry is predicated on the relationship between the researcher and the research focus being itself a relationship of power. Since power is complex and a single definition is not desirable, different actor‐orientated frames of power were used for the data analysis. The results show that authors are more likely to work with issues of power to (i.e., agency), power over, and empowerment, rather than resistance or disempowerment . Demonstrating the effect of such frames, these proportions change according to whether the research focuses on equity, effectiveness, or participation. For instance, power to is strongly associated with effectiveness, while disempowerment is associated more with equity. Together with other identified patterns, our review shows that researchers frame power in adaptation in ways that constitute biases and blind spots. Attention to particular frames of power can limit attention to important dynamics within adaptation processes. Both the content and context to which the identified frames are applied suggest structural trends in adaptation research that require increased attention. Since researchers' frames of power influence both research outcomes and broader adaptation‐power relations, the results indicate that reflexivity is needed to improve both adaptation research and practice. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : Researchers' implicit conceptual frames of power matter in climate change adaptation research, with clear implications for practice. We demonstrate associations between researchers' frames of power and adaptation processes and outcomes.